![If \: \alpha \: and \: \beta \: are \: the \: zeroes \: of \: the \: polynomial \: f(x) = x2 - P(x +1) - c then\ \ \ \ ( \alpha + 1)( \beta + 1) = If \: \alpha \: and \: \beta \: are \: the \: zeroes \: of \: the \: polynomial \: f(x) = x2 - P(x +1) - c then\ \ \ \ ( \alpha + 1)( \beta + 1) =](https://tex.z-dn.net/?f=If+%5C%3A+%5Calpha+%5C%3A+and+%5C%3A+%5Cbeta+%5C%3A+are+%5C%3A+the+%5C%3A+zeroes+%5C%3A+of+%5C%3A+the+%5C%3A+polynomial+%5C%3A+f%28x%29+%3D+x2+-+P%28x+%2B1%29+-+c++then%5C+%5C+%5C+%5C+%28+%5Calpha+%2B+1%29%28+%5Cbeta+%2B+1%29+%3D)
Answer with explanation
Answers
Answered by
1
Step-by-step explanation:
We have,
Now,
So,
Similar questions